PESANTREN DAN MADRASAH DALAM LINTASAN POLITIK PENDIDIKAN DI INDONESIA - M. Fahim Tharaba (MANAGERE : Indonesian Journal of Educational Management, 2020)
This research aims to excavate the meaning and substance contained in the entire thought of Islamic boarding school and madrasah in the politic of educational in Indonesia. The method of research use bibliografic research with content analysis. The results of study revealed that Islamic boarding school and madrasah in politic of education in Indonesia experienced tremendous dynamics, especially starting from the colonial period, namely the pioneering stages of the establishment of madrasah; the old order. Islamic boarding school and madrasah are not only recognized, but also in the form of coaching and guidance; the new order, madrasah is aimed to build an intact national education system completely. Therefore, madrasah has extra burden of considerable weight, because it must provide curriculum of level public school completely, he also had to provide the essential materials of Islam that had been taught; the reformation period. Islamic boarding school and madrasah diniyah received recognition juridically; and the period after reform. Islamic boarding school and madrasah are faced with a touch of technology.